x(m+2)+y(m-2)=z(m-7)form

Simple and best practice solution for x(m+2)+y(m-2)=z(m-7)form equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x(m+2)+y(m-2)=z(m-7)form equation:


Simplifying
x(m + 2) + y(m + -2) = z(m + -7) * form

Reorder the terms:
x(2 + m) + y(m + -2) = z(m + -7) * form
(2 * x + m * x) + y(m + -2) = z(m + -7) * form

Reorder the terms:
(mx + 2x) + y(m + -2) = z(m + -7) * form
(mx + 2x) + y(m + -2) = z(m + -7) * form

Reorder the terms:
mx + 2x + y(-2 + m) = z(m + -7) * form
mx + 2x + (-2 * y + m * y) = z(m + -7) * form

Reorder the terms:
mx + 2x + (my + -2y) = z(m + -7) * form
mx + 2x + (my + -2y) = z(m + -7) * form

Reorder the terms:
mx + my + 2x + -2y = z(m + -7) * form

Reorder the terms:
mx + my + 2x + -2y = z(-7 + m) * form

Reorder the terms for easier multiplication:
mx + my + 2x + -2y = z * fmor(-7 + m)

Multiply z * fmor
mx + my + 2x + -2y = fmorz(-7 + m)
mx + my + 2x + -2y = (-7 * fmorz + m * fmorz)
mx + my + 2x + -2y = (-7fmorz + fm2orz)

Solving
mx + my + 2x + -2y = -7fmorz + fm2orz

Solving for variable 'm'.

Reorder the terms:
7fmorz + -1fm2orz + mx + my + 2x + -2y = -7fmorz + fm2orz + 7fmorz + -1fm2orz

Reorder the terms:
7fmorz + -1fm2orz + mx + my + 2x + -2y = -7fmorz + 7fmorz + fm2orz + -1fm2orz

Combine like terms: -7fmorz + 7fmorz = 0
7fmorz + -1fm2orz + mx + my + 2x + -2y = 0 + fm2orz + -1fm2orz
7fmorz + -1fm2orz + mx + my + 2x + -2y = fm2orz + -1fm2orz

Combine like terms: fm2orz + -1fm2orz = 0
7fmorz + -1fm2orz + mx + my + 2x + -2y = 0

The solution to this equation could not be determined.

See similar equations:

| 4m-29=-26+7m | | -1/2y+1/5=-1/6 | | (485-)(42+2)5+230=g | | 42=3m | | (7x)/7 | | 6(6t+1)-10=t-(t+3) | | -4/5d=20 | | x(m+2)+y(m-2)=z(m-7) | | 8x+6y+4z=6 | | -4x-3y=25 | | 64.5g=-25.8 | | -4/7-5/3v=-1/3 | | 0.30(x+100)+0.50x=46 | | 8x^2+3x+5=0 | | 5.50(75+x)=1100 | | |x-3|+2=2 | | 15/125 | | -3/8z=-12 | | 3t+1/7=t+4/14+t-2/14 | | 8x+8y+5z=1 | | |x-1|=0 | | 2x+12/7=3x-1 | | (-x^2)-12=0 | | t=r+k/4(w) | | 8(-5+4m)= | | 5w^2+19w-1=0 | | 7((x+4)/7)-4 | | 5w^2+19w-1=o | | .20x+50=.30x | | t=r+k/4*w | | x-60+y=1362 | | |6x|=18 |

Equations solver categories